New Ukrainian school: experience and prospects (Actual Problems of Psychology in Educational Institutions, 2020)
Abstract. The article discusses the essence and quality of moderneducational space as a factor in the formation of the New Ukrainian School.Psychological and pedagogical trends and conditions for optimizing theeducational process are analyzed in accordance with the tasks defined bythe State standard of primary education. The importance of organizing anoptimal classroom in the classroom according to the laws of ergonomics andaesthetics is disclosed. The urgency of observing the principle of continuityof preschool and primary education is noted. The author emphasizes thatthe competency-based approach to learning is an important resource forthe personal development of a child. The conclusion is drawn about theneed for systemic reform of primary education in the dimensions of theNUS.
Keywords: success; success situation; success motivation; junior schoolchild; New Ukrainian School